2016
DOI: 10.1523/jneurosci.2309-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Prolyl Oligopeptidase Restores Spontaneous Motor Behavior in the α-Synuclein Virus Vector–Based Parkinson's Disease Mouse Model by Decreasing α-Synuclein Oligomeric Species in Mouse Brain

Abstract: Decreased clearance of ␣-synuclein (aSyn) and aSyn protein misfolding and aggregation are seen as major factors in the pathogenesis of Parkinson's disease (PD) and other synucleinopathies that leads to disruption in neuronal function and eventually to cell death. Prolyl oligopeptidase (PREP) can accelerate the aSyn aggregation process, while inhibition of PREP by a small molecule inhibitor decreases aSyn oligomer formation and enhances its clearance via autophagy in different aSyn overexpressing cell types and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 74 publications
6
63
0
Order By: Relevance
“…It is likely that the aSyn load produced by AAV was high enough to not allow cellular protein clearance machinery to entirely degrade excess aSyn. However, PREP inhibition still had a beneficial effect on mouse motor behavior, which was associated with decrease in soluble higher aSyn oligomer counts in the PREP inhibitor treated animals [75]. Similarly, we had shown that soluble higher aSyn oligomers are reduced in aSyn overexpressing cells after PREP inhibition [73].…”
Section: Prep Inhibition Enhances Asyn Clearance By Inducing Autophagymentioning
confidence: 55%
See 1 more Smart Citation
“…It is likely that the aSyn load produced by AAV was high enough to not allow cellular protein clearance machinery to entirely degrade excess aSyn. However, PREP inhibition still had a beneficial effect on mouse motor behavior, which was associated with decrease in soluble higher aSyn oligomer counts in the PREP inhibitor treated animals [75]. Similarly, we had shown that soluble higher aSyn oligomers are reduced in aSyn overexpressing cells after PREP inhibition [73].…”
Section: Prep Inhibition Enhances Asyn Clearance By Inducing Autophagymentioning
confidence: 55%
“…Similarly, we had shown that soluble higher aSyn oligomers are reduced in aSyn overexpressing cells after PREP inhibition [73]. Proteinase K (PK)resistant aSyn inclusions were not decreased as efficiently as soluble forms after PREP inhibition in the mouse AAV aSyn overexpression model [75], and this suggests that it might be related to the inability of the protein degradation pathway to degrade PK-resistant aSyn inclusions after they have been formed.…”
Section: Prep Inhibition Enhances Asyn Clearance By Inducing Autophagymentioning
confidence: 97%
“…In vitro specificity studies revealed that KYP‐2047 was a potent and selective inhibitor of POP, and currently, it is widely used in in vitro and in vivo studies. (Bainbridge et al, ; Myöhänen, Hannula, et al, ; Svarcbahs, Julku, & Myohanen, ). We found that POP overexpression increased progesterone production in primary luteal cells (Figure d).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the time length of the experiment, 8 weeks, could have been a factor in TH loss, since while there was a functional effect, it may have taken longer to observe a more robust loss of TH across all animals. Also, at 8 weeks, enough potentially toxic aggregates may not be present in the brain to cause loss of TH neurons, such as in an AAV mouse study that only started to show Proteinase K‐resistant α‐syn at 8 weeks (Svarcbahs, Julku, & Myohanen, ). However, several AAV‐α‐syn experiments have been conducted for 8 weeks or less and observed TH loss (Gombash et al, ; Gully et al, ), though how many animals showed the loss is less clear.…”
Section: Discussionmentioning
confidence: 99%